Moral Methodology of the Vatican II according to Louis Janssens - Sujoko, Albertus (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2012)
By moral methodology of Vatican II, I mean the way of moral thinking or moral approach used in the documents of Vatican II. Louis Janssens is of the opinion that Vatican II documents are characterized by a personalistic way of moral thinking. This way of doing moral theology bases itself on the human person adequately considered in all of his/her dimensions which build up his/her dignity as the human person. This article explains some characters of personalistic moral methodology, namely that dynamic and dialogical aspect of moral approach which characterizes both Janssens's moral theology and Vatican II way of thinking. Moral theology must be dynamic as is life from which it derives. One cannot just repeat moral norms to every situation. Life situation is always changing and causing new moral questions which needs new and correct moral solutions. The most important criterion is whether or not the moral answers to new moral problem are promotive for the real good of the person, that is making the person better and better as human being. The council of Vatican II and the moral theologian Louis Janssens are the examples of how to deal with a new changing modern world with such a creative and dynamic engagement in making dialog with new situations.